Parties in the digital jungle - I. A. Lavrov (Вестник университета)
The development of digital technology, Internet communications and social media affects all areas of public life. Politics is no exception. In today’s world, social media are becoming not only a means of transmitting information, but also the habitat of millenials and zoomers. Year after year, more and more digital natives (M. Prensky’s term) are gaining the right to vote in elections. This fact cannot avoid political parties, which are beginning to adapt the use of social media to their own informational and campaigning needs. Social platforms present an opportunity to form a loyal community, which will follow the political process through the prism of the values of the preferred party, and eventually become politically active in the coming elections. The author questions whether the role of social media is so great, what determines it and whether young people engaged in politics through social media are really capable of changing the course of the political process. To answer these questions, a sociological study was conducted that included an analysis of the official accounts of political parties and their members in the main social media operating in Russia. The audience engagement index was compiled and calculated in relation to the results of the elections to the State Duma of the 8th convocation in 2021.